2021
DOI: 10.4081/jphr.2021.2186
|View full text |Cite
|
Sign up to set email alerts
|

Chest Pain Symptoms Differences between Diabetes Mellitus and Non-Diabetes Mellitus Patients with Acute Coronary Syndrome: A Pilot Study

Abstract: Background: Chest pain is considered one of the crucial indicators in detecting acute coronary syndrome (ACS), and one of the most common complaints frequently found in hospitals. Atypical characteristics of chest pain have prevented patients from being aware of ACS. Chest pain symptoms have become ambiguous, particularly for specific parameters, such as gender, diabetes mellitus (DM), or other clinical conditions. Therefore, it is critical for high-risk patients to have adequate knowledge of specific symptoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…Further analyses revealed, that the observed associations did not apply to younger AMI patients (age 54 and younger) with no significant associations between diabetes and specific symptoms at all. Also prior studies have reported that diabetes goes along with less AMI symptoms including typical chest pain as well (5)(6)(7)(8)(9)(10). A current review/meta-analysis specifically analyzing chest pain symptoms and diabetes came to the same conclusion (17).…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Further analyses revealed, that the observed associations did not apply to younger AMI patients (age 54 and younger) with no significant associations between diabetes and specific symptoms at all. Also prior studies have reported that diabetes goes along with less AMI symptoms including typical chest pain as well (5)(6)(7)(8)(9)(10). A current review/meta-analysis specifically analyzing chest pain symptoms and diabetes came to the same conclusion (17).…”
Section: Discussionmentioning
confidence: 52%
“…Therefore, early diagnosis and timely treatment of diabetes are especially important. Prior studies indicated that AMI patients with diabetes less often report typical chest pain symptoms and some other typical AMI symptoms (5)(6)(7)(8)(9)(10). Thus, diagnostics of AMI in diabetic patients would be impeded.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding patients with diabetes mellitus suffering from AMI, Manistamara et al 27 reported that these patients tend to rate their pain as less intense compared with non-diabetic patients. In contrast, we found that patients with diabetes mellitus in general rate their chest pain as higher, regardless of AMI occurrence.…”
Section: Discussionmentioning
confidence: 99%